Description of a new species of Rismethus Fleutiaux, 1947 from Republic of Benin with a key to the known African species (Coleoptera, Elateridae, Agrypnini) - (:unkn) unknown (My University, 2023)
A new species of Rismethus Fleutiaux, 1947 from West Africa (Republic of Benin) is described. It is allied to R. riesei Platia, Biondi & Sechi, 2020 known from Gabon for the third antennal article only a little shorter than the second but can be separated for the smaller and stouter body because of elytra shorter compared to pronotum and differences in the male genitalia.
Keywords: African Research